Penyuluhan Tentang Konsep Pembangunan Berbasis Masyarakat Di Desa Dusun Sawah Kecamatan Curup Utara Kabupaten Rejang Lebong - Hidayat, Rahmat Al; Hermika, Hermika; Harisandi , Nova Rizki (Universitas Dehasen Bengkulu, 2021)
Counseling on the concept of community-based development in Dusun Sawah Village, North Curup Sub-district, Rejang Lebong Regency, is an important effort in introducing and practicing development approaches that involve active community participation. This research aims to analyze the effectiveness of such extension in improving the understanding and involvement of the community in the local development process. The research method used was qualitative with a case study approach. Data were obtained through participatory observation, in-depth interviews, and analysis of relevant documents. The results showed that the extension program succeeded in improving the community's understanding of the concept of community-based development and encouraging their involvement in various development activities in the village. Factors such as the sustainability of the extension program, active participation of community leaders, and support from the local government played an important role in its success. The implication of this study is the need for continuity of counseling and strengthening the role of community leaders in supporting the implementation of the concept of community-based development to achieve sustainable development at the local level.